Neoadjuvant chemotherapy for borderline resectable and upfront resectable pancreatic cancer increasing overall survival and disease-free survival? - Fossaert, Violette; Mimmo, Antonio; Rhaiem, Rami; Rached, Linda J.; Brasseur, Mathilde; Brugel, Mathias; Pegoraro, Francesca; Sanchez, Stephane; Bouché, Olivier; Kianmanesh, Reza; Piardi, Tullio (Frontiers in Oncology, 2022)
Background Pancreatic ductal adenocarcinoma (PDAC) is the most common pancreatic neoplasm. Surgery is the factual curative option, but most patients present with advanced disease. In order to increase resectability, results of neoadjuvant chemotherapy (NAC) on metastatic disease were extrapolated to the neoadjuvant setting by many centers. The aim of our study was to retrospectively evaluate the outcome of patients who underwent upfront surgery (US)-PDAC and borderline (BR)-PDAC, and those resected after NAC to determine prognostic factors that might affect the outcome in these resected patients. Methods One hundred fifty-one patients between January 2012 and March 2021 in our department were reviewed. Epidemiological characteristics and pre-operative induction treatment were assessed. Pathological reports were analyzed to evaluate the quality of oncological resection (R0/R1). Post-operative mortality and morbidity and survival data were reviewed. Results One hundred thirteen patients were addressed for US, and 38 were considered BR and referred for surgery after induction chemotherapy. The pancreatic resection R0 was 71.5% and R1 28.5%. pT3 rate was significantly higher in the US than BR (58,4% vs 34,2%, p= 0.005). The mean OS and DFS rates were 29.4 months 15.9 months respectively. There was no difference between OS and DFS of US vs BR patients. N0 patients had significantly longer OS and DFS (p=<0.001). R0 patients had significantly longer OS (p=0.03) and longer DFS (P=0.08). In the multivariate analysis, the presence of postoperative pancreatic fistula, R1 resection, N+ and not access to adjuvant chemotherapy were bad prognostic factors of OS. Conclusions Our study suggests the benefits of NAC for BR patients in downstaging tumors and rendering them amenable to resection, with same oncological result compared to US.